ANALISIS KEMANDIRIAN ANAK USIA 4-5 TAHUN DI TAMAN KANAK KANAK NURUNNAJAH DESA LAPOK AUR KECAMATAN PEMAYUNG KABUPATEN BATANG HARI - Juliyana Juliyana; Kasmiati Kasmiati; Rizki Surya Amanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study employed a qualitative approach using a descriptive method. The research subjects were children aged 4–5 years in Group A of Nurunnajah Kindergarten. Data were collected through observation, interviews, and documentation. Data analysis involved data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation.The findings revealed that most children demonstrated a good level of independence in various activities, such as putting on and taking off their shoes, eating independently, completing tasks without assistance, tidying up toys, and going to the restroom independently. However, some children had not yet achieved optimal independence, as they still needed assistance while eating, were unable to put on or remove their shoes independently, and required support from parents or teachers in completing tasks. Children's independence was reflected in physical abilities, self-confidence, responsibility, discipline, emotional control, and decision-making skills.